ВДОСКОНАЛЕННЯ ОСНОВ ІМПУЛЬСНОГО ПЕРЕТВОРЕННЯ ЄМНІСНИМ МЕТОДОМ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ У ВИСОКОЧАСТОТНУ МЕХАНІЧНУ - Петрищев, О.М.; Ноздрачова, К.Л.; Сучков, Г.М.; Мигущенко, Р.П.; Кропачек, О.Ю.; Плєснецов, С.Ю. (Інститут електродинаміки НАН України, Київ, 2019)
Closed solutions of electrostatic and electrodynamics problems are formed in metals for a piecewise-homogeneous medium, where half-space is filled with metal of finite values having electrical conductivity and magnetic permeability being implemented within the framework of a mathematical model for capacitive type sensor when converting electrical energy into high-frequency mechanical (ultrasonic). It is shown that a disk transducer of a capacitive type excites forces acting normally on the surface of an electrically conductive product. A quantitative assessment of Coulomb forces for the surface density is carried out. The main factors determining a disk converter sensitivity of capacitive type are stated. Capacitive transducers should be used for measuring, control and diagnostic equipment. References 10, figures 3.